PENGARUH KUALITAS LAYANAN MOBILE BANKING TERHADAP LOYALITAS NASABAH DENGAN MENGELOLA KEUANGAN PRIBADI SEBAGAI VARIABEL MODERATING - Della Amelina; Eliza Noviriani; Roshani, Roshani (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to analyze the effect of service quality and ability to manage personal finances on customer loyalty of Bank Kalbar Mobile application users. The research method used is quantitative descriptive with a survey approach. Sampling was carried out using a purposive sampling technique to 97 respondents, which were obtained using the Slovin formula. Data processing was carried out using SmartPLS 4 through the Structural Equation Modeling (SEM) approach. The results of the study indicate that service quality has a positive and significant effect on customer loyalty, as well as the ability to manage personal finances. However, the variable of managing personal finances is not able to moderate the relationship between service quality and customer loyalty. Simultaneously, service quality and managing personal finances are able to explain the effect on customer loyalty by 71.8%. This finding emphasizes the importance of improving services and financial education to strengthen customer loyalty. Keywords: Service Quality, Customer Loyalty, Managing Personal Finances, Mobile Banking